Perlindungan Hukum bagi Konsumen di Sektor Perbankan: Tantangan dan Solusi di Era Digital - Raymma, Aracely (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Legal protection for consumers in the banking sector has become an important issue along with the rapid development of digital technology that is changing the landscape of financial services. This article aims to analyze the challenges faced by consumers in banking transactions in the digital era and explore solutions that can be applied to improve consumer protection. Technological developments, such as mobile banking services, digital payments, and the use of artificial intelligence (AI) in customer data analysis, bring benefits, but also give rise to new risks such as threats to personal data security, cyber fraud, and inequality in access to services. This article examines existing regulations, such as the Consumer Protection Law and Bank Indonesia policies, as well as banking practices that can help protect consumers, including information transparency, strengthening cybersecurity systems, and implementing the principle of prudence. Through a legal analysis approach and case studies, this article provides recommendations for improving regulations and increasing the role of supervisory institutions in order to maintain a balance between digital innovation and consumer rights protection in the banking sector.